Ictal SPECT of Thalamocortical Coupling in a Patient with Frontal Absence - Kanemura, H.; Sano, F.; Sugita, K.; Aihara, M. (Neuropediatrics, 2011)
Petit mal absence has been reported with 3-Hz generalized spike-and-wave discharges induced by secondary bilateral synchrony. Absence seizure may be present in patients with frontal lobe epilepsy. The thalamic rhythmogenic mechanisms responsible for spike-and-wave discharges have been investigated, providing a better understanding of the underlying anatomico-physiological mechanisms. We report the thalamocortical coupling in a patient with frontal absence by performing synchronous ictal single photon emission computed tomography (SPECT) analysis. Ictal SPECT revealed thalamic hyperperfusion combined with ipsilateral frontal cortical hyperperfusion in the patient. Moreover, lateral indexes of cerebral blood flow in the frontal region and thalamus were higher than those from non-epileptic control subjects. Thalamocortical coupling was thus revealed by ictal SPECT. Frontal absences should be considered as a secondarily generalized epilepsy syndrome originating from the frontal regions. The thalamus may play a crucial role as a pacemaker of rhythmic electroencephalographic activities such as secondary bilateral synchronous discharges in patients with frontal absences.
Keywords: frontal absence; secondary bilateral synchronous discharge; thalamus; thalamocortical coupling; ictal SPECT